Evaluation of the pain perception associated with one-jaw and two-jaw total maxillary arch distalization (TMAD) in class II division 1 patients: A randomized controlled trial (Journal of Hama University, 2024)
Evaluating levels of pain associated with any treatment is a crucial aspect in assessing the effectiveness of any treatment.The aim of the current study was to evaluate the levels of pain associated with total maxillary arch distalization (TMAD) using a one-jaw and two-jaw mechanics, compared to traditional treatment involving extraction of upper premolars and en-mass retraction of anterior teeth in camouflage orthodontic treatment for Class II Division 1 malocclusion patients.Forty-five patients (20 males, 25 females) with Class II Division 1 malocclusion according to the Angle classification were included in the current study. They were randomly assigned to three groups: the first group was treated with TMAD using mini-screw implants between the second premolars and first maxillary molars; the second group was treated with TMAD using inter-maxillary elastics between the maxillary canines and mini-screws between the first and second mandibular molars; and the third group received traditional treatment involving extraction of premolars and mass retraction of anterior teeth with mini-screws between the second premolar and first maxillary molar and en-mass retraction of the anterior teeth. Spontaneous and on biting pain levels were evaluated immediately after force delivery, as well as after 6, 24, 48 hours, one week, and two weeks, using the 11-point Numeric Rating Scale (NRS). The mean values of spontaneous pain and pain during chewing in the 2-Jaw TMAD group (3.7 and 6, respectively) were significantly higher than the mean values of spontaneous pain in the 1-Jaw TMAD group (1.7 and 3, respectively), which were also significantly higher than the mean values calculated for the traditional extraction group (1 and 2). The peak pain occurred in the two TMAD groups at 24-48 hours, while it peaked at 6 hours in the control group (P
Keywords: total maxillary arch distalization; orthodontic pain; mini-screws; class II division 1 malocclusion.